Dividends, Interest, Profits, Wages, 1923-35^1 - Kreps, T. J. (Quarterly Journal of Economics, 1935)
Introduction, 561.— I. Labor incomes, dividends and interest: all corporations, 563. — What is national income? 566.— Choice of a base for comparison, 571.— Dividends and interest payments vs. net earnings, 573.— II. The manufacturing industries taken separately, 575. — Further evidence on dividend payments, 581.— Corporate capitalization during the depression, 584.— III. Confusion of profits with interest and dividends, 585.— Different experience of these items, 586.— The fortunate exceptions, 590.— Computation of profits, 590. — Reduction in interest payments, 593.— Net profits in 1933 and 1934, 595.— Deficits, 599.— Conclusions, 599.